2022
DOI: 10.1371/journal.pone.0272262
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea and anatomical structures of the nasomaxillary complex in adolescents

Abstract: The aim of the present study was to reveal the associations between skeletal and soft tissue features of the nasomaxillary complex and development and severity of obstructive sleep apnea (OSA) in adolescents. A total of 100 adolescents (mean age, 14.9 ± 1.4 years; age range, 13–17 years) were enrolled. All participants underwent full-night polysomnography and had an assessment of size and position of the tongue, tonsillar size, body mass index (BMI), and circumference of the waist, neck, and hip. The skeletal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…At the same time, the palatal height itself is not a reliable indicator of maxillary contraction [ 12 ], and its role in the development of OSA is still a topic of discussion. A recent review [ 27 ] reported that palatal height does not have a significant correlation with the onset of OSA. In the present study, the inverse correlation between ODI and palatal height may be due to the reduced overall palatal surface available for the tongue, as also confirmed by the significant decrease in the palatal area reported in the current findings.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the palatal height itself is not a reliable indicator of maxillary contraction [ 12 ], and its role in the development of OSA is still a topic of discussion. A recent review [ 27 ] reported that palatal height does not have a significant correlation with the onset of OSA. In the present study, the inverse correlation between ODI and palatal height may be due to the reduced overall palatal surface available for the tongue, as also confirmed by the significant decrease in the palatal area reported in the current findings.…”
Section: Discussionmentioning
confidence: 99%
“…We chose an effect size of 0.4 based on a similar previous study. 29 SPSS 22.0 (IBM, Armonk, NY) was used for statistical analysis. To determine intra-examiner reliability, the same examiner repeated the measurements on 10 sets of randomly selected CBCT data after a 2-week interval.…”
Section: Discussionmentioning
confidence: 99%
“…Power analysis indicated that a total sample size of 100 participants, comprising 20 subjects in the symmetric group and 80 subjects in the asymmetric groups who were involved in this study for post hoc analysis, would yield a statistical power of 92.4 at a significance level of 0.05, with an effect size of 0.4. We chose an effect size of 0.4 based on a similar previous study 29 …”
Section: Methodsmentioning
confidence: 99%
“…The typical anatomic relationships inside the oral cavity may also be altered by malocclusion and changes in the location or tone of the soft palate, which can restrict the airway and exacerbate OSA symptoms [17,18]. Furthermore, increased airway blockage during sleep may result from changes in tongue position brought on by changes in tooth structure [19,20]. Furthermore, mouth breathing can worsen dry mouth and increase the risk of dental caries.…”
Section: Introductionmentioning
confidence: 99%